HUBUNGAN ANTARA TASAWUF DAN SYARI’AT PERSPEKTIF PEMIKIRAN AHMAD SIRHINDI - Izomiddin Izomiddin (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2014)
In Ahmad Sirhindi's era, India was stepping over serious crisis stage of knowledge and Islamic teaching practices. Sultan Akbar had legalized national policy by doing reactualization of Islamic teachings in nation’s life. On the other hand, group of Sufis disseminated various beliefs and teachings, which were considered as deviation from pure Islamic teachings by some of intellectual figures at that time including Ahmad Sirhindi. That deviation originated from polytheistic India. However, some other western oriented intellectual figures acknowledged those religious teaching practices. This article attempts to discuss Ahmad Sirhindi’s tasawuf thought by using social-historical approach.ملخص: فى عصر حياة سرهندى سارفرع من قارات هندى الوسطى قد مضت مرحلتها فى العلم وتعاليم الدين. وقد صادق سلطان أكبر على الحكمة الوطنية بأعمال تعاليم الإسلام فى حياة الإجتماعية والحكومة، وبينما فى آية اخرى نشّر الصوفيون عقائد وتعاليمهم التّى نظر العلماء حينئذ – منها السرهندى – قد انحرف من حقيقة التعاليم الإسلامية. وذلك الإنحراف يسبّب من كثرة الألوهية بالهندى. ولكنّ بعض العلماء المتخرّجين من الغرب يصدّقون تلك التعاليم. ستعترض هذه المقالة عن فكرة التصوّف لاحمد السرهندى بالمراقبة التاريخية الإجتماعية.